Experimental investigation of methanol compression ignition in a high compression ratio HD engine using a Box-Behnken design. (1st December 2017) - Shamun, Sam; Haşimoğlu, Can; Murcak, Ahmet; Andersson, Öivind; Tunér, Martin; Tunestål, Per
Abstract: Methanol is an alternative fuel offering a lower well-to-wheel CO2 emission as well as a higher efficiency, given that the fuel is derived from biomass. In addition to reduced CO2, methanol does not emit soot particles when combusted which is a great advantage when attempting to reduce NO X levels due to the effectively non-existing NO X -soot trade-off. The engine setup used was a Scania D13 engine modified to run on one cylinder, utilizing a high compression piston with a rc of 27:1. This study analyzes the effects of four control parameters on gross indicated efficiency and the indicated specific emissions; CO, THC and NOX . The control parameters chosen in this work was common rail pressure (PRAIL ), EGR, λ and CA50, running at 6 bar IMEPG and 1200 rpm. The effects of the control parameters on performance and emissions was analyzed using a surface response method of the Box-Behnken type. Predictive mathematical models were obtained from regression analysis performed on the responses from the experiments. The highest gross indicated efficiency achieved was ∼53%, when a high level of EGR was applied together with the combustion phasing set to its low level at CA50 = 6 CAD ATDC. The control parameters influencing the CO emissions are λ and the interaction between PRAIL and λ, while THC is only controlled by PRAIL and EGR. NO X emissions was, as expected, influenced mainly by EGR and λ, although PRAIL and CA50 also had minor effects. The effect of increased PRAIL, increased THC emissions which in its turn reduced the gross indicated efficiency. Throughout the experiment, THC concentration never decreased below ∼150 ppm due to utilization of high rc in combination with the volatility of methanol. It was also concluded that a rc = 27 is rather high if operation flexibility is required, especially at the higher load range.